Governance of the water-energy-food nexus for an integrated implementation of the 2030 Agenda: Conceptual and methodological framework for analysis - Srinivasa Reddy Srigiri; Ines Dombrowsky (Deutsches Institut für Entwicklungspolitik (DIE), 2021)
Implementing the 2030 Agenda requires an improved understanding of the interdependencies among the Sustainable Development Goals (SDGs) and targets and the design and implementation of coherent policies across different levels and sectors. The water-energy-food (WEF) nexus has emerged over the past decade as a useful concept to reduce trade-offs and increase synergies in promoting goals of water, energy and food security. While WEF scholarship substantiates the biophysical interlinkages and calls for increased and effective coordination across sectors and levels, knowledge about the conditions for effective coordination is lacking. We aim to contribute to this understanding by conceptualising WEF nexus governance from an analytical perspective as a polycentric system and by developing a framework based on the concept of networks of adjacent action situations (NAASs). The interdependence among transactions for pursuing WEF securities by actors in the differing action situations generates a need for coordination in changing or sustaining institutions, policy goals and policy instruments that guide actions leading to sustainable outcomes. Coordination is achieved through arrangements based on cooperation, coercion and competition. Coordination in complex social-ecological systems is unlikely to be achieved by a single governance mode but rather by synergistic combinations of such modes. Particular coordination arrangements that emerge in a given context depend on the distribution of authority, information and resources within and across interlinked decision-making centres. Integrating the political ecology-based conceptualisations of power into the analytical framework further extends the governance analysis to include the influence of power relations on coordination. Methodological innovation in delineating action situations and identifying the unit of analysis as well as integrating different sources and types of data are required to operationalise the conceptual framework.
Keywords: 330